Das Dritte Reich und die Juden : die Jahre der Verfolgung 1933-1939, die Jahre der Vernichtung 1939-1945 - Friedländer, Saul, 1932-; Friedländer, Saul, 1932- (Verlag C.H. Beck, 2017)
Giving considerable emphasis to an immense array of recently published material and a wealth of new archival findings, Saul Friedlander describes and interprets the steadily increasing anti-Jewish persecution in Germany after the 1933 Nazi accession to power. He demonstrates the interaction between intentions and contingencies, between discernible causes and changing circumstances. Friedlander shows how Nazi ideological objectives and tactical policy decisions enhanced one another and always left an opening for ever more radical moves.